Inhibitory Effects of Garcinia cambogia Extract on CYP2B6 Enzyme Activity - Yu, Jun Sang; Choi, Min Sun; Park, Jong Suk; Rehman, Shaheed Ur; Nakamura, Katsunori; Yoo, Hye Hyun (Planta Medica, 2017)
This study assessed the inhibitory effects of Garcinia cambogia extract on the cytochrome P450 enzymes in vitro. G. cambogia extract was incubated with cytochrome P450 isozyme-specific substrates in human liver microsomes and recombinant CYP2B6 isozyme, and the formation of the marker metabolites was measured to investigate the inhibitory potential on cytochrome P450 enzyme activities. The results showed that G. cambogia extract has significant inhibitory effects on CYP2B6 activity in a concentration-dependent manner. Furthermore, the inhibition was potentiated following preincubation with NADPH, indicating that G. cambogia extract is a time-dependent inhibitor of CYP2B6. Meanwhile, hydroxycitric acid, the major bioactive ingredient of G. cambogia extract, did not exhibit significant inhibition effects on cytochrome P450 enzyme activities. G. cambogia extract could modulate the pharmacokinetics of CYP2B6 substrate drugs and lead to interactions with those drugs. Therefore, caution may be required with respect to concomitant intake of dietary supplements containing G. cambogia extract with CYP2B6 substrates.
Keywords: Garcinia cambogia; Clusiaceae; CYP; drug metabolism; drug interaction